PRODUCTION INCREASE OF MUNG BEANS (Vigna radiata L.) USING CHICKEN CAGES AND GROWTH REGULATORS (ZPT) - Wismaroh sanniwati Saragih (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2022)
Mung bean (Vigna radiata L.) is one of the legume commodity crops which is allocated more in the household and industrial consumption sector as a raw material for food and beverages. However, its current production is still unable to meet national demand. Therefore, this study aims to increase mung bean production by using chicken manure and plant growth regulator (PGR) as well as an alternative in nourishing soil nutrients because they do not contain chemical compounds. The research method used a randomized block design factorial with two treatments. The first treatment of chicken manure application, consisting of A0 (0 g/plot) as control; A1 (2000 g/plot); A2 (4000g/plot); and A3 (4000 g/plot). The second treatment of PGR applications, consists of Z0 (0 cc/plant) as control; Z1 (0.5 cc/plant); Z2 (1.0 cc/plant); and Z3 (1.5 cc/plant). The material mung bean seeds of the Vima 1 variety. The parameters observed were the number of pods per sample and the number of pods per plot. To determine the effect of the treatment of the parameters observed a statistical test was carried out with the analysis of variances (ANOVA), if it had a significant effect then it was continued with the Duncan Multiple Range Test (DMRT) at 5% level. The results showed that the application of chicken manure and PGR had a very significant effect on the observed parameters. The best treatment is the use of chicken manure A2 (4000 g/plot) and PGR Z3 (1.5 cc/plant) as an alternative to increasing mung bean production.